Algoritma Spotted Hyena Optimizer pada Capacitated Vehicle Routing Problem - Prayoga Yudha Pamungkas; Nur Mayke Eka Normasari (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
Transportation is used in the delivery of goods from one location to another, contributing costs to the final price of a product or service. Efficiency is needed to reduce transportation costs, one of which can be done by optimizing transportation routes. Vehicle Routing Problem (VRP) is a problem that is often referred to to find the optimal route from a source to several points at minimal cost. VRP is evolving into a complex problem as the number of consumers to visit increases. This complexity causes VRP to be included in the combinatorial optimization which has a lot of configuration in finding the shortest route. In this study, VRP was completed with a metaheuristic approach using the Spotted Hyena Optimizer (SHO) algorithm. The use of SHO in capacitated vehicle routing problems (CVRP) is based on the results of research by the originator of SHO which is able to achieve convergent rate faster than other algorithms. SHO on CVRP produces better solutions or shorter total distances than genetic algorithms, ant colony, and particle swarm optimization by using the Augeraat dataset as a comparison of the final results in each algorithm.